Changes in the bacterial and microeukaryotic communities in the bioreactor upon increasing heavy metal concentrations - Aceves-Suriano, Claudia E.; Montoya-Ciriaco, Nina; Hernández-Guzmán, Mario; Hernández-Martínez, Gabriel R.; Navarro-Noya, Yendi E.; Thalasso, Frédéric; Dendooven, Luc (Frontiers in Environmental Chemistry, 2023)
Amplicon sequencing of 16S rRNA and 18S rRNA was used to investigate how the bacterial and microeucaryotic communities were affected in an activated sludge bioreactor incrementally contaminated with Ni, Cu and Zn from 0% to 100% of IC50, as previously determined, while an uncontaminated bioreactor served as control. The chemical oxygen demand (COD) was on average 90% in the uncontaminated bioreactor but dropped to 49% when the heavy metal concentration was 100% IC50. The bacterial community in the uncontaminated bioreactor was dominated by Alphaproteobacteria (mostly Agrobacterium and Brevudimonas) when the heavy metal concentrations were low and Bacteroidetes (mostly Sphingobacterium) when the highest amounts of heavy metal were applied. Members of Ciliophora, Ascomycota and Basidiomycota dominated alternatively in the uncontaminated bioreactor but Ascomycota (mostly Fusarium) in the contaminated bioreactor. It was found that increased concentrations of Ni, Cu and Zn altered the bacterial and microeucaryotic communities and some putative metabolic functions.